Growth and Convergence of Social Sectors' Expenditure in Indian States: Upshots from Neoclassical Growth and Panel Unit Roots Models. (June 2020) - Das, Ramesh Chandra; Ivaldi, Enrico
In a world of having large part suffering from the inadequacies of basic needs and inter-class and inter-regional income disparities, investing upon the development of different social sectors from the state exchequers have been one of the top agendas of the policymakers. It is not a different issue for the states and provinces of the developing countries like India. Besides having positive roles on economic betterment, spending on social expenditures sometimes work in favour of the ruling political parties to gain confidence from the voters. The states thus compete in this area. Under this background, the present study attempts to examine whether the states of India are converging in social sector's expenditure for the period 1980–81 to 2017–18. Applying the neoclassical growth and panel unit roots models the study observes unambiguously that there are absolute and conditional β convergence and σ convergence in per capita social expenditure among the states. JEL Classification: H72, O470, C23, O530